Impact of implementing the Meyer-Neldel behavior of carrier emission pre-factors in solar cell and optical detector modeling - Rubinelli, Francisco Alberto (2015)
The Meyer-Neldel behavior reported for the emission probabilities of electrons and holes was included in our code, replacing the gap state capture cross sections of the Shockley-Read-Hall formalisms with capture cross sections containing an exponential function of the trap energy depth. The Meyer-Neldel energies for electrons and holes are the slopes of these exponentials. Our results indicate that emission probabilities of neutral states no deeper than approximately 0.45 eV and 0.37 eV from the conduction and valence band edges, respectively, can show a Meyer-Neldel behavior only, while on the other hand, its implementation in deeper gap states makes the replication of experimental J-V curves of p-i-n solar cells and detectors impossible. The Meyer-Neldel behavior can be included in all neutral capture cross sections of acceptor-like tail states without affecting the J-V characteristics, while it cannot be included in all capture cross sections of neutral donor-like tail states and/or defect states without predicting device performances below the experimental figures, that become even lower when it is also included in charged capture cross sections. The implementation of the anti Meyer-Neldel behavior at tail states gives rise to slightly better and reasonable device performances.